Impacts of Digital Financial Inclusion on Urban-rural Income Disparity : A Comparative Study of the Eastern and Western Economic Regions in China - Jing, Liu; Puah, Chin Hong; Mohammad Affendy, Arip; Jong, Meng Chang (2022)
A comparative analysis on the impact of digital financial inclusion on the income disparity between urban and rural areas in the eastern and western economic zones of China. In this paper, the static panel approach has been employed to investigate the impacts of digital financial inclusion on urban and rural income disparity in eastern and western economic zones in China by using Stata software. A comparative analysis also will be conducted to examine the impacts of the digital financial inclusion on the urban and rural income disparity between western and eastern areas in China. The empirical results show that the seven selected independent variables chosen in this study can reduce the income disparity in eastern and western areas of China. In general, the inclusion of digital financial is having a greater impact in minimizing the income gap in western region than eastern region in China as shown in Model 1 to Model 6. The outcomes show that all the selected variables presenting the higher influence degree on the income disparity in western China than eastern areas of China except the credit index, it shows the influence of the western region (0.10%) is lower than that of the eastern zone (0.11%). The empirical results of this paper can as a reference for the government and policy maker in reducing the urban and rural income disparity through digital financial inclusion in eastern and western areas of China.